Complex Primary Total Hip Replacement in a Patient with Sickle Cell Disease and Contralateral Poliomyelitis: A Case Report and Review of Literature - Ayekoloye, Charles; Oladiran, Ajibola Babatunde; Omololu, Ajibade Babatunde (Nigerian Journal of Orthopaedics and Trauma, 2019)
Sickle cell haemoglobinopathy (SCH) and neurological sequelae of childhood poliomyelitis are still relatively common in this environment. The non-paralytic limb in polio patients is subjected to abnormal stresses due to excessive weight-bearing load, leg length discrepancy, pelvic obliquity and abnormal gait mechanics. We present this case to highlight the challenges of managing such a case and present our experience. A 47-year-old female with SCH presented with left-sided avascular necrosis (AVN) of the head of the femur and right-sided post-polio paralysis. Limb length discrepancy was 1.5 cm with a longer left lower limb. Oxford hip score (OHS) = 25 and SF12 = 16. Packed cell volume (PCV) was 20%. Radiographs revealed a destroyed left hip with secondary osteoarthritis, partial collapse, lateral subluxation and metaphyseal sclerosis. She had non-cemented left total hip arthroplasty via Hardinge approach. One-month post-operative scores were OHS = 38, SF12 = 24. Three-month follow-up scores were OHS = 46 and SF12 = 30. AVN poses a major burden. Combination with post-polio paralysis and the risk of infection with encapsulated organisms create a complex interplay of challenges. Peri-operative management requires meticulous monitoring, care and prevention of sickling crisis. Uncemented implants gave better results with fewer complications. Limb shortening at arthroplasty increases dislocation risk; so, length should be maintained. Coexisting post-polio paralysis and SCH is rare but challenging. The non-paralytic limb is subjected to excessive abnormal forces. Excellent results and low complication rates are achievable if meticulous peri-operative management, appropriate choice of cementless implants and maintenance of length are done. Ensuring adequate fixation of implants at surgery reduces risk of loosening. Rehabilitation must take the risk of falls into account. Pre-operative planning and optimisation, meticulous surgical technique and cementless implants are keys to success.